Description of a new species of the genus Xyrosaris Meyrick (Lepidoptera: Yponomeutidae) from the Far East of Russia with notes on congeneric species - Ponomarenko, Margarita G.; Beljaev, Evgeny A. (Zootaxa, 2023)
A new species, Xyrosaris insularis sp. n., was found in the Far East of Russia. Most of the specimens were obtained through the rearing of larvae that fed on Celastrus orbiculatus Thunb. (Celastraceae). The genetic distances between the mtCOI sequences in X. insularis and congeneric species are in the range 1.2–13.9%. Minimal genetic distance (1.2%) was discovered between new species and X. lichneuta Meyrick from Shaanxi (China), which is lower than the standard mtCOI barcoding threshold of 2% for species delineation, but both taxa differ well in the genital morphology. The description of a new species is accompanied by illustrations of variations in the pattern, by the genitalia of both sexes, and by larva on its host plant.